Prevalence and determinants of household solid waste management practice among residents of the city corporations of Dhaka, Bangladesh - Irsat Jahan; Kh. Farhad Hossain; Syed Sharaf Ahmed Chowdhury; Afnan Mohd Shafiullah; Sadia Shafi; Azaz Bin Sharif (PLoS ONE, 2026)
Solid waste management (SWM) has emerged as a global concern, posing critical environmental and public health challenges. Dhaka’s ranking as the second most polluted city in the world between 2018 and 2021 highlights the need for a more sustainable waste management system. Household solid waste is mismanaged, as evident from illegal dumping in unauthorized places, scattered garbage and overflowing waste bins on the roads, and clogged drains creating severe environmental health hazards. This study aimed to identify the prevalence and determinants of household SWM practices among residents of the city corporations of Dhaka, Bangladesh. A cross-sectional survey was conducted from June to July 2025 among 496 residents using a pre-tested structured questionnaire administered through face-to-face interviews. Descriptive statistics were used to summarise participants background characteristics and their levels of knowledge, perception, and practice related to household SWM. Associations between independent variables and SWM practice were examined using chi-square tests, and multivariable binary logistic regression was performed to determine potential factors associated with good practice. The prevalence of good household SWM practice was 47.18%. Knowledge (AOR = 1.23; 95% CI: 1.12–1.35), perception (AOR = 1.14; 95% CI: 1.06–1.22), and exposure to information regarding solid waste management (AOR = 1.91; 95% CI: 1.27–2.89) were significantly associated with good practice. Overall, the findings indicate that household SWM practices among residents of the city corporations of Dhaka remain suboptimal. Increasing access to SWM-related information through targeted communication strategies may enhance household-level SWM practices.